Transition‐Metal‐Catalyzed Selective Functionalization of C(sp3)−H Bonds in Natural Products. Issue 16 (14th February 2018) - Karimov, Rashad R.; Hartwig, John F.
Abstract: Direct functionalization of natural products is important for studying the structure–activity and structure–property relationships of these molecules. Recent advances in the transition‐metal‐catalyzed functionalization of C(sp 3 )−H bonds, the most abundant yet inert bonds in natural products, have allowed natural product derivatives to be created selectively. Strategies to achieve such transformation are reviewed. Abstract : Direct derivatization : Direct functionalization of natural products is important for studying their structure–activity and structure–property relationships. Recent advances in the transition‐metal‐catalyzed functionalization of C(sp 3 )−H bonds have shown that natural product derivatives can be selectively produced. Strategies for achieving such transformations are discussed.